ANALYSIS OF MTs STUDENT ERRORS IN SOLVING HOTS QUESTIONS BASED ON MATHEMATICAL REASONING ABILITY - Syifa Fadilla; Hafriani Hafriani (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2023)
Reasoning ability is one of the abilities that students must have through high-order thinking processes to solve problems. However, students have not been able to solve problems that require high-order thinking and students have not been able to examine the problems given. This study aims to describe errors and factors that cause students to make mistakes made by MTs students in solving HOTS questions based on mathematical reasoning abilities. This research uses a qualitative approach with a descriptive type. The subjects of this study were 2 students with high category of mathematical reasoning abilities, 2 students in medium category, and 2 students in low category. The research instrument consisted of the researcher himself and test questions as the main instrument followed by an interview guide and tape recorder. Data collection was carried out by written tests and interviews. The technique for checking the validity of the data uses time triangulation, namely giving STKPM1 and STKPM2 at different times. The results of this study indicate that students with high abilities are able to solve HOTS questions correctly without any errors, students with moderate abilities have errors in doing mathematical manipulation, compiling evidence or giving reasons for the correctness of solutions and drawing conclusions from statements. The factor that causes students to make these mistakes is that students do not understand the problems given and make mistakes in calculating. Meanwhile, students with low ability categories have errors in making assumptions, manipulating mathematics, compiling evidence or giving reasons for the correctness of solutions and drawing conclusions from statements. The factor that causes students to make these mistakes is not understanding the problem given.Keywords: Error Analysis, HOTS Questions, Mathematical Reasoning Ability